Predictors of professional quality of life among nursing staff following the Taiwan Formosa Fun Coast explosion. Issue 2 (March 2020) - Lu, Ming-Hsiu; Weng, Ling-Tzu; Chen, Ya-Lin; Lin, Chin; Wang, Chih-Hsin; Pan, Hsueh-Hsing
Highlights: Length of service year in nursing and perceived stress level was important predictors of compassion satisfaction among the nurses. Age and perceived stress level were important predictors of compassion fatigue and burnout among the nurses. It has been proposed that the level of stress among nurses should be lowered to improve the professional quality of life. Abstract: Purpose: The Formosa Fun Coast Explosion was a major public disaster that caused international shock. Nursing staff made an all-out effort to care for patients injured in the explosion, and this may have caused a lot of stress among nurses. This study aimed to explore the predictors of professional quality of life among nursing staff experiencing major disaster events. Material and Methods: This descriptive cross-sectional study was conducted in a medical center in Northern Taiwan in 2016. A total of 165 nurses were enrolled using convenience sampling. Data were collected on the demographic- and work-related characteristics of nurses, and the Perceived Stress Scale and Professional Quality of Life Scale were administered. Analyses included descriptive statistics and regression. The threshold for statistical significance was set at p  < 0.05. Results: The nurses' length of service in nursing ( β  = −0.26, p  = 0.029) and perceived stress level ( β  = 0.15, p  = 0.002) were important predictors of compassion satisfaction, while their age ( β  = 0.42, p  = 0.033) and perceived stress level ( β  = 0.20, p  = 0.020) were important predictors of compassion fatigue. Compassion fatigue was divided into burnout and secondary trauma. Nurses' age ( β  = 0.18, p  = 0.044) and perceived stress level ( β  = 0.14, p  < 0.001) were the key predictors of burnout. However, there were no significant predictors of secondary trauma among nurses. Conclusions: Based on the present findings, it is proposed to reduce the level of stress among nurses to improve their professional quality of life.